The The Application of Risk Identification in the Safety Production of Electric Power Enterprises - Ma, Lei (Pacific International Journal, 2023)
With the continuous maturity and application of electric power technology, the electric power system has gradually moved towards the direction of large power grid, ultra-high voltage, large unit and intelligence, and the operation safety problems of electric power enterprises continue to emerge. In the safety risk management of electric power enterprises, the first thing is to evaluate the risks existing in the work of power grid. Risk assessment needs to monitor the working condition of the power system and evaluate the possible risks in the actual working process. Strengthening the risk assessment of power system and improving the safety risk assessment level of power system are of great theoretical significance and engineering application value for the future development of power system. Only by establishing the safety risk assessment system of power system can we make scientific and standardized countermeasures when emergencies occur. In the process of power engineering safety risk management, the primary task is to identify the risk factors correctly and comprehensively. Only by accurately and efficiently identifying risk factors, can we correctly grasp the law of development and change of potential risks, correctly measure the size of risks, and choose effective methods to deal with corresponding risks according to the actual situation.